Response of Rubber tree GT 1, PB 235, and PB 217 clones to different doses of mineral fertilizers in south-west Côte d'Ivoire - Jean Lopez, ESSEHI; francis, Soumahin Eric; Joseph, Alle Yamoussou; djézou, konan; antoine, koffie; samuel, obuayeba (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2025)
The permanent export of soil nutrients by rubber latex systematically leads to a notorious impoverishment of the soil and consequently to a decrease in rubber production from the plantations. To do this, three studies on the mineral fertilization of rubber trees clones GT 1, PB 235 and PB 217 were carried out on plots belonging in South-west Côte d’Ivoire. The research was carried out under the ecological conditions of the area, on ferrallitic soils of granitic origin, to compare the effect of nitrogen, phosphate, and potassium fertilizers, applied alone or in combination, and different doses of N-P-K-Mg (8-4-20-4) on the radial isodiametric growth, yield, and nutrient content leaves of rubber trees. Fertilizer applications were carried out on elementary plots of 84 to 100 trees in two experimental designs (factorial and Fischer block). obtained revealed that the application of increasing doses of nitrogen, phosphate and potassium fertilizers had no apparent effect on rubber tree growth parameters trees. Small gains in rubber yields have observed, ranging from 1.5 to 5%, regardless of the rubber clone. These fertilizer applications, without prior knowledge of the physico-chemical status of the soil, have sometimes caused a decrease in production by creating or accentuating imbalances between soil minerals. Based on these results, we recommend that fertilization policies on rubber plantations should consider the level of local soil fertility and the nature, frequency, and timing of fertilizers applications, but without excess, to gain a better appreciation of the effect of fertilizers on the agronomic parameters of rubber trees.